Integrating latent variables in discrete choice models: How higher-order values and attitudes determine consumer choice - Dirk Temme; Marcel Paulssen; Till Dannewald (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
Integrated choice and latent variable (ICLV) models represent a promising new class of models which merge classic choice models with the structural equation approach (SEM) for latent variables. Despite their conceptual appeal, to date applications of ICLV models in marketing are still rare. The present study on travel mode choice clearly demonstrates the value of ICLV models to enhance understanding of choice processes. In addition to the usually studied directly observable variables such as travel time, we show how abstract motivations such as power and hedonisms as well as attitudes such as a desire for flexibility impact on travel mode choice. Further, we can show that it is possible to estimate ICLV models with the widely available structural equation modeling package Mplus. This finding is likely to encourage wider usage of this appealing model class in the marketing field.
Keywords: C25; C51; C87; M31; R41; 330; Hybrid choice models; Mode choice; Values; Value-attitude hierarchy; Mplus; Konsumentenverhalten; Diskrete Entscheidung; Multivariate Analyse; Verkehrsmittelwahl; Soziale Werte; Theorie; Deutschland